Identification of the PKR Nuclear Interactome Reveals Roles in Ribosome Biogenesis, mRNA Processing and Cell Division. Issue 8 (August 2014) - Blalock, William L.; Piazzi, Manuela; Bavelloni, Alberto; Raffini, Mirco; Faenza, Irene; D'Angelo, Antonietta; Cocco, Lucio
<x xml:space="preserve">Abstract</x> The double‐strand RNA‐dependent protein kinase, PKR, plays a central role in inflammatory/chronic stress‐mediated pathologies such as cancer, diabetes, and neuro/muscular degenerative diseases. Although a significant amount of research has been conducted to elucidate the role of PKR signaling in the cytosol, only recently has attention been paid to the role of PKR in the nuclear compartment. Previously our group reported that phosphorylated forms of PKR are present in the nucleus of acute leukemic cell lines, representing a reservoir of active kinase that responds to stress. Using the CCRF‐CEM acute T‐cell leukemia cell line, a PKR‐specific inhibitor, co‐immunoprecipitation and a proteomics approach, which included affinity purified mass spectrometry analysis (AP/MS), we identified the proteins present in active and inactive PKR nuclear complexes. Of the proteins identified in the PKR complexes, sixty‐nine (69) were specific to the active complex, while thirty‐eight (38) were specific to the inactive complex. An additional thirteen (13) proteins associated specifically with both complexes. The majority of the proteins identified are involved in, ribosome biogenesis, RNA splicing, mRNA stability, gene expression, cell cycle, or chromatin organization, including several with known significance to normal hematopoiesis and/or hematological disease. In agreement with the AP/MS data, basal‐ or over‐expression of PKR under normal growth conditions favored cell proliferation in the tested cell lines, whereas pharmacological inhibition of PKR or shRNA‐mediated knock‐down did not. PKR was also found to influence the isoform and the level of expression of the proto‐oncogene MYC. J. Cell. Physiol. 229: 1047–1060, 2014. © 2013 Wiley Periodicals, Inc.